Pancreatic involvement in fatal human leptospirosis: clinical and histopathological features - Daher, Elizabeth De Francesco; Brunetta, Denise Menezes; Silva Júnior, Geraldo Bezerra da; Puster, Rainardo Antonio; Patrocínio, Régia Maria do Socorro Vidal (Revista do Instituto de Medicina Tropical de São Paulo, 2003)
Hyperamylasemia has been reported in more than 65% of patients with severe leptospirosis, and the true diagnosis of acute pancreatitis is complicated by the fact that renal failure can increase serum amylase levels. Based on these data we retrospectively analyzed the clinical and histopathological features of pancreas involvement in 13 cases of fatal human leptospirosis. The most common signs and symptoms presented at admission were fever, chills, vomiting, myalgia, dehydratation, abdominal pain and diarrhea. Trombocytopenia was evident in 11 patients. Mild increased of AST and ALT levels was seen in 9 patients. Hyperamylasemia was recorded in every patient in whom it was measured, with values above 180 IU/L (3 cases). All patients presented acute renal failure and five have been submitted to dialytic treatment. The main cause of death was acute respiratory failure due to pulmonary hemorrhage. Pancreas fragments were collected for histological study and fat necrosis was the criterion used to classify acute pancreatitis. Histological pancreatic findings were edema, mild inflammatory infiltrate of lymphocytes, hemorrhage, congestion, fat necrosis and calcification. All the patients infected with severe form of leptospirosis who develop abdominal pain should raise the suspect of pancreatic involvement.